Precalculus (6th Edition)

Published by Pearson
ISBN 10: 013421742X
ISBN 13: 978-0-13421-742-0

Chapter R - Review of Basic Concepts - R.7 Radical Expressions - R.7 Exercises - Page 76: 119



Work Step by Step

To solve the item mentally, note that: $\dfrac{\sqrt[3]{15}}{\sqrt[3]{5}}=\sqrt[3]{3}$ (because of the quotient rule for radicals) Thus, the given expression is equivalent to: $=\sqrt[3]{3} \cdot \sqrt[3]{9}$ $\\=\sqrt[3]{27}$ (because of the product rule for radicals) Since $27=3^3$, then $\sqrt[3]{27}=\sqrt[3]{3^3} = 3$ Thus, the given expression is equal to $3$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.